Linking carbon and nitrogen metabolism to depth distribution of submersed macrophytes using high ammonium dosing tests and a lake survey. (25th August 2013) - Yuan, Guixiang; Cao, Te; Fu, Hui; Ni, Leyi; Zhang, Xiaolin; Li, Wei; Song, Xin; Xie, Ping; Jeppesen, Erik
Summary: Strategies of carbon (C) and nitrogen (N) utilisation are among the factors determining plant distribution. It has been argued that submersed macrophytes adapted to lower light environments are more efficient in maintaining C metabolic homeostasis due to their conservative C strategy and ability to balance C shortage. We studied how depth distributions of 12 submersed macrophytes in Lake Erhai, China, were linked to their C‐N metabolic strategies when facing acute NH 4 + dosing. NH 4 + dosing changed C‐N metabolism significantly by decreasing the soluble carbohydrate (SC) content and increasing the NH 4 + ‐N and free amino acid (FAA) content of plant tissues. The proportional changes in SC contents in the leaves and FAA contents in the stems induced by NH 4 + dosing were closely correlated (positive for SC and negative for FAA) with the colonising water depths of the plants in Lake Erhai, the plants adapted to lower light regimes being more efficient in maintaining SC and FAA homeostasis. These results indicate that conservative carbohydrate metabolism of submersed macrophytes allowed the plants to colonise greater water depths in eutrophic lakes, where low light availability in the water column diminishes carbohydrate production by the plants.